Global trends and current status in pheochromocytoma: a bibliometric analysis of publications in the last 20 years - Huang, Bi-ling; Liu, Qi; Teng, Yuan-yuan; Peng, Shu-qin; Liu, Ze; Li, Ming-liu; Liang, Jie-yu; Zhang, Yi; Wang, Min (Frontiers in Endocrinology, 2023)
Objective: Pheochromocytoma is a rare catecholamine-producing neuroendocrine tumour originating from the chromaffin cells of the adrenal medulla or extra-adrenal paraganglia. However, there are few bibliometric studies on Pheochromocytoma. Therefore, this study was employed to summarize the global trends and current status in pheochromocytoma by bibliometric analysis. Materials and Methods: The Web of Science (WOS) core collection database was searched for publications relating to pheochromocytoma from 2001 to 2021. Bibliometric analysis was used to examine the data, and Microsoft Excel was utilized to create bar graphs. In addition, VOSviewer was used to carry out co-authorship analysis, co-citation analysis and co-occurrence analysis. CiteSpace was used to analyze the keywords citation bursts. Results: A total of 8,653 publications published in 1,806 journals by 38,590 authors in 6,117 organizations from 100 countries/regions were included in our study. Among them, USA was the leading countries in terms of total publications and sum of time cited, whereas Eunice Kennedy Shriver Natl Inst Child Hlth & Hum was the leading institutions. The main publications for pheochromocytoma-related articles were Journal of clinical endocrinology ＆metabolism. Pacak karel and Eisenhofer Graeme were the main contributing authors. The studies on pheochromocytoma could be grouped into five clusters: Treatment, Mechanism, Etiology, Radiology and Hormones study. Moreover, the radiology study, etiology study and some specific keywords such germlines mutation, mesenchymal stem-cells, autophagy, neuroinflammation, neurotoxicity, and hemodynamic instability, may become the hot spots of future. Conclusion: Although the number of articles on pheochromocytoma has fluctuated slightly over the past 20 years, there has been an overall upward trend. In general, precision medicine research on pheochromocytoma, especially metastatic pheochromocytoma, in terms of diagnosis, treatment, and etiology will be a hot research topic in the future. This study helps to understand the research perspectives, hot spots and trends of pheochromocytoma and provide new insight and a basis for future pheochromocytoma research quickly.